Where are we at with women’s self-determination? (BioLaw Journal - Rivista di BioDiritto, 2025)
The article examines the evolution of legislation and key constitutional jurisprudence regarding women's freedom of self-determination in choices concerning their bodies, with particular attention to the issues of abortion, medically assisted reproduction, prostitution and surrogacy. Specifically, it highlights how, despite progress, a paternalistic approach persists, hindering the full realization of women's rights and preventing them from freely exercising their self-determination.
Keywords: Women’s self-determination; abortion; medically assisted reproduction; prostitution; surrogacy